Pemberdayaan Ekonomi Masyarakat Terintegrasi dan Berdaya Saing di Desa Pelem, Kecamatan Kertosono - Wathon, A (Lembaga Yasin AlSys, 2025)
This community service research is motivated by the urgent need for an integrated and competitive economic activity center in Pelem Village, Kertosono District, Nganjuk Regency, due to the lack of effective economic hubs that has resulted in limited income growth, insufficient local employment opportunities, and low village economic competitiveness. The primary objective of this study is to explore untapped local economic potential, identify barriers to community economic development, and design and implement a sustainable, citizen-driven economic center model. The research employs Participatory Action Research (PAR) using a qualitative approach. Data were collected through focus group discussions, in-depth interviews, observation, and documentation involving 25 MSME actors, 10 community leaders, and 5 village officials. The findings indicate that the village’s main potential lies in the food processing, handicrafts, and local tourism sectors; however, development is hindered by limited market access, low product innovation, and weak financial management capacity. These findings support Community Development Theory and the Local Economic Cluster model. The study recommends establishing a village digital marketplace, providing product diversification training, and forming a village cooperative as strategic steps for local economic empowerment. The implications of this research include contributions to the literature on community-based economic development and opportunities for ongoing evaluation of the long-term impact of the implemented empowerment model.